Analisis Pengaruh Rasio Keuangan dan Ukuran Perusahaan terhadap Probabilitas Financial Distress - Arda , Fauziah; Hindasah , Lela (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction – financial distress is a condition in which a company experiences default on its creditors. The success or failure of a company can be seen by analyzing financial ratios. This study aims to analyze the effect of financial ratios and company size on the probability of financial distress in property and housing companies listed on the IDX (Indonesian Stock Exchange) for the 2016-2020 period. Methodology/Approach – using a logistic regression model with a sample of 43 property and real estate companies using purposive sampling as the data collection method. Findings – The results of the study show that the liquidity ratio and leverage ratio have a positive effect on the probability of financial distress. Activity ratios and profitability ratios have a negative effect on the probability of financial distress. Firm size has no effect on the probability of financial distress. Originality/ Value/ Implication – This study found that the liquidity ratio has an inverse effect on financial distress in property and real estate companies.